O intérprete de tribunal no Brasil: peritus peritorum? - Novais Néto, Lourival (2009)
The practice of court interpreting in Brazil has been commonly done by professionals with bilingual skills that are nominated interpreters ad hoc, whenever no sworn translators are available in the jurisdictions. Although much theoretical researches have increased in the field of court interpreting in the last twenty years, court interpreters still work as individuals and independents, ignoring the studies directed toward of their activity. Court interpreting terminology is widely used to mention any type of legal interpreting; however, the courtroom is only one of the many contexts in which the legal interpreting occurs. This research aims to reflect on the intricacy on face-to-face interaction process in a natural context of speech: the bilingual courtroom, in which the interpreter has the function to interpret from one language to other and also within the mother language, whose difficult process is performed in real time. This thesis dialogs with Forensic Linguistics, which has the purpose to study the relation between Law and Language that converge topics in common, in order to indicate possible resolutions of legal problems; and it also dialogs with the Interacional Sociolinguistics. Studies by Goffman (1967, 1975, 1979), Brown & Levinson (1987) and Gumperz (1982) are highlighted. This thesis presents characteristics of one of the qualitative methods based on ethnographic research: the natural observation (Adler & Adler, 1998), and the analysis is focus on the data extracted from Novais Néto (2002). In the context of the current reality of court interpreting in Brazil, this work explores mainly the features of interpreter s questions when mediating the interaction between a judge, speaker of Portuguese idiom, and a defendant, speaker of English idiom, in a testimony of a Brazilian Court of Justice. The action of the interpreter is mainly determined by the Criminal Proceeding Code, Term of Commitment, and Criminal Code. However, there is no guarantee the fulfillment of these rules, due to the judge s linguistic ability in foreign language. Therefore, the interpreter assumes a similar judge alignment in the hearing, regarding to conversational power, not legal: a peritus peritorum, a classic expression from the forensic field used specifically to the judge as expert of the connoisseurs (Barros, 2008:32)